How the National Flood Insurance Program (NFIP) Works - Regina Fegan; Michael T. Olexa (EDIS, 2003)
The Federal Insurance and Mitigation Administration (FIMA) makes flood insurance available in areas where the appropriate public body has adopted adequate floodplain management regulations for its flood-prone areas. Community participation is voluntary, although some states require NFIP participation as part of their floodplain management program. Communities who wish to participate in the NFIP must fulfill two phases: phase 1, Emergency Program of the NFIP and phase 2, Regular Program of the NFIP. This document, IFAS publication DH0436, was published June 1998, revised May 2003. It is part of The Disaster Handbook, a component of the Comprehensive Disaster Preparedness and Recovery Education Module.